KONTRIBUSI PERHATIAN ORANGTUA DAN KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU AGRESIF PADA SISWA MENENGAH ATAS (SMA) - Desep Pria Pandri; Ridho Rismi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Aggressive behavior is an act that causes others to suffer, thus causing physical and psychological distress. In addition, the explanation above is also reinforced by the Indonesian Child Protection Commission (KPAI) which describes that the trend of socializing with children in education this year has increased quite a lot due to aggressive behavior. Aggressive behavior is caused by a lack of parental attention and low peer conformity. The role of parents can also provide related matters in responding to aggressive behavior as a whole so that individuals have the deployment or concentration of energy or mental strength of parents towards their children's social activities with full awareness for the formation of good behavior. This study aims to reveal (1) aggressive behavior in Senior High Schools (SMA), parental attention and peer conformity, (2) the contribution of parental attention and peer conformity individually or together to aggression in Senior High Schools (SMA). The study uses a quantitative method of the descriptive correlation type. The study population is Senior High Schools (SMA) registered in the odd semester of the 2024/2025 academic year. The research sample was Senior High School (SMA), which was selected using the Purposive sampling technique using the Slovin formula. The findings from the results of this study explain that (1) the description of parental attention is in the medium category, (2) peer conformity is in the medium category, (3) aggressive behavior is in the high category, (4) there is a significant contribution between parental attention and aggressive behavior of 0.18%, (5) there is a significant contribution between peer conformity and aggressive behavior of 39.3%, (6) there is a significant relationship between parental attention and peer conformity together with aggressive behavior of 42.1%. This means that parental attention and peer conformity are factors that contribute to reducing and decreasing aggressive behavior in Senior High Schools (SMA). The data of this study means that the higher the parental attention and peer conformity, the lower the aggressive behavior in Senior High Schools (SMA). In relation to the results of this study, researchers can make suggestions: 1) Senior High Schools (SMA) can utilize Guidance and Counseling services to shape positive behavior, 2) Guidance and Counseling teachers should collaborate with school personnel, parents and Senior High Schools (SMA) in preventing and reducing aggressive behavior, and 3) the principal as a leader should be able to assist Guidance and Counseling teachers in establishing good cooperation with parents and other school parties, so as to prevent and reduce aggressive behavior.